Affective Theory of Mind as a residual ability to preserve mentalizing in amnestic Mild Cognitive Impairment: A 12-months longitudinal study - Rossetto, Federica; Isernia, Sara; Cabinio, Monia; Pirastru, Alice; Blasi, Valeria; Baglio, Francesca (Frontiers in Neurology, 2022)
Introduction Theory of Mind (ToM) decline has been outlined in people with amnestic Mild Cognitive Impairment (aMCI), but evidence from longitudinal studies is lacking. This longitudinal study aims to investigate changes in cognitive and affective ToM performance in an aMCI sample (n = 28; 14 females, mean age = 76.54 ± 4.35). Method Participants underwent two steps of neurocognitive evaluation, at the baseline (T1) and 12-month follow-up (T2), to obtain their global cognitive level and both affective (Reading the Mind in the Eyes test, ET) and cognitive (Strange Stories, SS) ToM profile. Then, participants were categorized into two groups based on ToM changes: people who worsened (ETΔ < 0; SSΔ < 0) and people who did not (ETΔ≥0; SSΔ≥0) at follow-up. Differences between groups in cognitive functions and ToM profiles at baseline have been investigated. Results Our results showed that 46% of subjects worsened in affective (ET) and 28% in cognitive (SS) ToM at follow-up. People who worsened in ET reported a statistically significantly higher performance in ET at baseline (p = 0.002) but not at follow-up than people who did not worsen. In contrast, subjects who worsened in SS showed a lower Immediate Free Recall (IFR, p = 0.026) and Delayed Free Recall (DFR, p = 0.028) score of the Free and Cued Selective Reminding test at baseline and at follow-up, a lower ET (p = 0.020) baseline score, a lower SS and MMSE level at follow-up than people who not worsened. About 71% of MCI subjects showed the same trend of evolution of the Mini-Mental State Examination and SS. Variables that significantly differed between groups have been inserted in a stepwise logistic regression to pilot explore predictors of affective and cognitive ToM evolution. Logistic regression showed ET at baseline (p = 0.015) as the only significant predictor of affective ToM evolution (R2 = 0.450), while both ET (p = 0.044) and memory performance (p = 0.045) at baseline significantly predicted cognitive ToM evolution (R2 = 0.746). Discussion In conclusion, our results support the role of affective ToM as a residual mentalizing ability in preserving the mentalizing level in people with aMCI.